Electrophysiological effects of felodipine on guinea pig papillary muscles - Zheng Ping; Shi Nian-Ci; Gong Qin-Yan; Yang Zao-Chen (Acta Pharmacologica Sinica; Vol 17, No 3 (May 1996): Acta Pharmacologica Sinica, 2016)
AIM: To determine whether felodipine (Fel) has Ca2+ channel blocking effect in mammalian myocardium in comparison with those of nifedipine (Nif) and verapamil (Ver). METHODS: The action potentials (AP), the slow AP and the inward slow Ca2+ currents of guinea pig papillary muscles were studied using intracellular microelectrodes and voltage-clamp techniques. RESULTS: Fel 1, 3, and 10 mumol.L-1 concentration-dependently shortened APD30, APD50, and APD90 of the AP, while Vmax and APA were not affected. The effect of Fel was not reversible on washout. At 0.1, 1, 3, and 10 mumol.L-1, Fel depressed Vmax, APA, APD30, APD50, and APD90 of the slow AP in a dose-dependent manner. The inward slow Ca2+ currents were reduced by Fel 3 mumol.L-1. APD30, APD50, and APD90 of the first AP after rest were still shortened by Fel. When the stimulation frequency was elevated, the effect of Fel on the AP and slow AP decreased. The effect of Fel 3 mumol.L-1 on the slow AP was abolished in preparation pretreated with trifluoperazine. The threshold concentrations of Nif and Ver for the inhibition of APD50 of the slow AP (P < 0.05) were 0.1 and 1 mumol.L-1, respectively. The effect of Ver 3 mumol.L-1 on the fast AP was not reversible on washout, but that of Nif 3 mumol.L-1 was. When the stimulation frequency was elevated from 0.5 to 2 Hz, the effect of Nif 3 mumol.L-1 on the fast AP was reduced, but that of Ver 3 mumol.L-1 was increased. CONCLUSION: Fel inhibited mainly the resting state of the cardiac Ca2+ channel. The potency of Fel was about the same as that of Nif and about 10 times more potent than that of Ver.